STUDYING THE IMPACT OF CLEANING TERM ON THE PRODUCTIVITY AND FEEDING VALUE OF S. SUDANENSE (RIPER) STAPF - Zhanatalapov, N. Zh (Science and education, 2019)
The most important link in the creation of a sustainable forage base in the rainfed lands of the Ural region is the obligatory cultivation of drought-resistant sorghum crops. Among this group of crops S. Sudanense (Riper) Stapf., is considered promising. According to the features of the photosynthetic cycle, Sudanese belongs to the type of C4, which determines its high productivity. In dry weather conditions, it provides stable yields compared to traditional fodder crops, is able to grow quickly after mowing, and can be used for silage, haylage, grass meal and green mass. However, despite all the advantages noted, the areas under crops of Sudanese grass are by now insignificant and its productivity in the West Kazakhstan region remains very low. The main reason is the lack of adaptive technologies for its cultivation. In this regard, the study of elements of the cultivation technology of Sudanese grass, which is the basis, the timing of harvesting the harvesting period: before cutting out, at the beginning of sprouting, flowering for the production of green fodder, haylage and for haymaking, determined the choice and relevance of the research topic. Важнейшим звеном создания устойчивой кормовой базы на богарных землях Приуралья является обязательное возделывание засухоустойчивых сорговых культур. Среди этой группы культур перспективной считается суданская трава - S. Sudanense (Riper) Stapf. По особенностям фотосинтетического цикла суданка относится к типу С4, что определяет ее высокую продуктивность. В засушливых погодных условиях она обеспечивает стабильность урожаев по сравнению с традиционными кормовыми культурами, способна быстро отрастать после скашивания и может быть использована на силос, сенаж, травяную муку и зеленую массу. Однако, несмотря на все отмеченные преимущества, площади посева суданской травы к настоящему времени незначительны и ее урожайность в Западно-Казахстанской области остается очень низкой. Основная причина - отсутствие адаптивных технологий ее возделывания. В связи с этим изучение элементов технологии возделывания суданской травы, основой которой является, сроки уборки сроков уборки: перед выметыванием, в начале выметывания, цветение для производства зеленых кормов, сенажа и для заготовки сена, определило выбор и актуальность темы исследований.
Keywords: научный журнал; сорговые культуры; отечественное издание; суданская трава; периодическое издание; кормовое сырье; журнал кксон; s. sudanense (riper) stapf; кормовые культуры; green fodder; haylage; harvest time